Spray Drying of a Subcritical Extract Using Marrubium vulgare as a Method of Choice for Obtaining High Quality Powder - Aleksandra Gavarić; Jelena Vladić; Rita Ambrus; Stela Jokić; Piroska Szabó-Révész; Milan Tomić; Marijana Blažić; Senka Vidović (Pharmaceutics, 2019)
White horehound (Marrubium vulgare L.), is a grey-leaved perennial herb, belonging to Lamiaceae family, distributed in Eurasia and northern Africa. Despite the fact that M. vulgare has been used since ancient times in treating diverse diseases, it is only in the last decade or so that scientists have been able to lay the foundation for its potential pharmacological actions from the results observed through the prism of ethnopharmacological use of this species. The novelty of this study was that subcritical water extraction, acknowledged as a powerful extraction technology to recover phenolic compounds, was coupled with spray drying. The subcritical horehound extract, obtained using optimal process parameters, was used as a liquid feed in spray drying. Maltodextrin was used as a carrier in a concentration of 10%. Thus, two M. vulgare powders, carrier-free and 10% MD, were produced. Comprehensive powders characterization was conducted in order to evaluate their quality. Results confirmed that spray drying can be used as a method of choice for obtaining high quality horehound powders which kept the amorphous structure constant after 6 months.